Manufactured light: mirrors in the Mesoamerican realm - Gallaga M., Emiliano, editor; Marc Gordon, Blainey, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2016)
Complex and time-consuming to produce, pyrite mirrors stand out among Prehispanic artifacts for their aesthetic beauty, their symbolic implications, and the complexity and skill of their assembly. Manufactured Light presents the latest archaeological research on these items, focusing on the intersection of their significance and use and on the technological aspects of the manufacturing processes that created them. The volume covers the production, meaning, and utilization of pyrite mirrors in various Mesoamerican communities. Chapters focus on topics such as experimental archaeology projects and discussions of workshops in archaeological contexts in the Maya, Central Mexico, and northwest Mexico regions. Other chapters concentrate on the employment and ideological associations of these mirrors in Prehispanic times, especially as both sacred and luxury items. The final chapters address continuities in the use of mirrors from Prehispanic to modern times, especially in contemporary indigenous communities, with an emphasis on examining the relationship between ethnographic realities and archaeological interpretations. While the symbolism of these artifacts and the intricacy of their construction have long been recognized in archaeological discussions, Manufactured Light is the first synthesis of this important yet under-studied class of material culture. It is a must-read for students and scholars of Mesoamerican archaeology, ethnography, religion, replicative experimentation, and lithic technology. Contributors include: Marc G. Blainey, Thomas Calligaro, Carrie L. Dennett, Emiliano Gallaga, Julie Gazzola, Sergio Gomez Chavez, Olivia Kindl, Brigitte Kovacevich, Achim Lelgemann, Jose J. Lunazzi, John J. McGraw, Emiliano Melgar, Joseph Mountjoy, Reyna Solis, and Karl Taube.--Provided by publisher.
Keywords: Material culture -- Southwest, New -- History -- To 1500; Material culture -- Mexico -- History -- To 1500; Mirrors -- Southwest, New -- History -- To 1500; Mirrors -- Mexico -- History -- To 1500; Indians of North America -- Material culture -- Southwest, New; Indians of Mexico -- Material culture; Indians of North America -- Southwest, New -- Antiquities; Indians of Mexico -- Antiquities; Southwest, New -- Antiquities; Mexico -- Antiquities